2020
DOI: 10.1002/adhm.201901502
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Impact of Antioxidant Hydrogel in Chronic Wound Healing

Abstract: The accelerating and thorough treatment of chronic wounds still represents a major unmet medical need owing to the complex symptoms resulting from metabolic disorder of the wound microenvironment. Although numerous strategies and bioactive hydrogels are developed, an effective and widely used method of chronic wound treatment remains a bottleneck. With the aim to accelerate chronic wound healing, many hydrogel dressings with antioxidant functions have emerged and are proven to accelerate wound healing, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
337
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(337 citation statements)
references
References 125 publications
0
337
0
Order By: Relevance
“…In this study, alginate, whose biosafety has been extensively verified, was employed to develop a biomaterial to solve the problem of repairing skin defects in complex clinical situations. 4 6 Self-healing hydrogels pose the property that self-heal after rupture. 7 , 8 Skin tissue is easily distorted, stretched, and deformed during the movement of the limb.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, alginate, whose biosafety has been extensively verified, was employed to develop a biomaterial to solve the problem of repairing skin defects in complex clinical situations. 4 6 Self-healing hydrogels pose the property that self-heal after rupture. 7 , 8 Skin tissue is easily distorted, stretched, and deformed during the movement of the limb.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hydrogels have a cooling and pain-relieving effect [1]. Hydrogel bases therefore offer great potential, as they can easily be combined with various substances that facilitate wound healing and/or have anti-inflammatory properties to promote healing in chronic wounds [28]. However, there is still a lot of educational work to be done by the treating physicians to make patients aware of these benefits and to establish ideal moist wound management as a standard approach even for minor wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BG can release Si ions to promote angiogenesis [ 13 ]. In addition, studies have shown that diabetic wound is often the most suitable place for microbial colonization, because of its hyperglycemia, which can easily give rise to wound infection [ 27 ]. CeO 2 can separate the outer membrane from the cytoplasmic membrane to inhibit the growth of bacteria [ 33 ].…”
Section: Discussionmentioning
confidence: 99%